Kashmiri-English Dictionary for Second Language Learners - Omkar N. Koul; Raina, S.N.; Roop Krishen Bhat (Central Institute of Indian Languages Mysore, 2000)
This is a Kashmiri-English Dictionary for Second Language Learners
Keywords: Kashmiri; Kashmiri-English Dictionary for Second Language Learners; Dictionary; Kashmiri; Kashmiri; English